2020
DOI: 10.1061/(asce)mt.1943-5533.0003036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Applicability of Biostimulated Calcium Carbonate Precipitation to Stabilize Clayey Soils

Abstract: Clayey soils with medium to high plasticity are prevalent in several parts of the world, causing billions of dollars in damage annually to various civil infrastructures. Several groundimprovement-techniques were employed to counteract this issue. However, these methods are impractical in certain situations and unsustainable in others due to their economic and environmental impacts. Microbial Induced Calcite Precipitation (MICP) could provide a more sustainable alternative. Researchers have successfully used MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…A study by Islam et al [39] revealed that, in general, MICP increased the UCS of clay soil, but the enhancing rate of UCS was below the threshold for some subgrade soils. However, the authors [39] indicated that the UCS of clayey soil might be increased beyond the threshold using additional treatment cycles. The enzyme-induced calcium carbonate precipitation (EICP) technique requires the urease enzyme rather than bacteria.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A study by Islam et al [39] revealed that, in general, MICP increased the UCS of clay soil, but the enhancing rate of UCS was below the threshold for some subgrade soils. However, the authors [39] indicated that the UCS of clayey soil might be increased beyond the threshold using additional treatment cycles. The enzyme-induced calcium carbonate precipitation (EICP) technique requires the urease enzyme rather than bacteria.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, biomaterials (bacteria and enzyme) [34] are utilized in bio-cementation techniques such as microbial-induced calcium carbonate precipitation (MICP) and enzyme-induced calcium carbonate precipitation (EICP) because of their "environmentally-friendly" features [35]. Microbially induced calcite precipitation (MICP) as a biomineralization method has been used for soil stabilization in previous studies [36][37][38][39]. A biochemical process occurs in the MICP method to improve soil properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies could extend the technique for stabilizing soft soils. For instance, Islam et al (2020) evaluated the effect of the clay content on MICP treatment. Their outcomes indicated that although the formation of calcium carbonate could marginally increase the unconfined compressive strength (UCS), the values attained after saturation were far below 50 KPa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the strength was contributed to by the cementing effect from clay soils and cementation homogeneity. The cementing effect from clay soils and better cementation homogeneity resulted in higher strengths than the results in [36,37].…”
Section: Ucs and Content Of Precipitationmentioning
confidence: 72%